Ethical Conduct in Business Organisations: The Opinion of Management Students in Gauteng - Geoff Goldman; Maria Bounds (Entrepreneurial Business and Economics Review, 2015)
This study investigates the perceptions that business and management students have towards ethical practices of businesses organisations in terms of the environment, their employees, community, regulators and competition.